A comparison of the skating technique in the curve for elite and junior sprint speed skaters - Yuda, J.; Michiyoshi, A. (ISBS - Conference Proceedings Archive (Konstanz), 2002)
The purpose of this study was to investigate the technical factors in the curve by comparing the skating techniques for elite (n=1) and junior (n=5) sprint speed skaters. They were videotaped with two VTR cameras at the mid portion of the inner second curve in the 500 m races. Three dimensional coordinates of the skaters were collected to calculate some kinematic parameters using a panning DLT technique. The onset of the push-off in the elite skater (left stroke; 44.0 %, right stroke; 42.0 %) was earlier than that of the junior skaters (53.6±2.5 %, 68.4±6.4 %, respectively). In the left stroke, the ankle of the free leg (right ankle) at the onset of the stroke for the elite skater placed more forward than that of the junior skaters. In addition, the elite skater pulled the free leg forward rapidly during the first half of the left stroke. These results indicate that hastening the timing of the skating movement is very important for skating in the curve lane under high skating velocity.